Hyper content e-module in information behavior course with the assistant of screencast - Riche Cynthia Johan; Gema Rullyana; Ardiansah Ardiansah (Journal of Education and Learning (EduLearn), 2022)
In the 21st century, continuous innovation and adaptation in every component of learning is required in education, both in the competency component, material content, strategy and media, as well as its evaluation. This study emphasized the development of an electronic or digital module in the information behavior course, it is one of the courses regarding the characteristics of the student activity level that accommodates information retrieval and strives to use appropriate information. The e-module design is developed utilize the 4D model by define, design, develop and disseminate. The participants of this research involved media experts, material experts and students of the Library and Information Science study program at two universities, which are are Universitas Pendidikan Indonesia and Universitas Negeri Malang, there are 20 people in total who used e-modules in limited dissemination on information behavior course. This research revealed the electronic module in the course, the emphasis of the module content design which is enriched with digital-based information sources or in another word called as hyper content that becomes a differentiator in presenting the module content, coupled with the power of audio and visual media or called as screencast. Through this research, lecturers able to prepare independent learning materials by utilizing digital technology.